Happiness management and social marketing in the age of artificial intelligence: an Itinerary towards social well-being and digital innovation - Ravina-Ripoll, Rafael; Bayardo Tobar Pesantez, Luis; Galiano-Coronil, Araceli; Galván Vela, Esthela (Editorial Tirant Lo Blanch, 2025)
This book is a collective work by the International University Network for Happiness. From an interdisciplinary perspective, this scientific research analyses how artificial intelligence can be integrated into social marketing and happiness management. It brings together academic contributions and research that examine the relationship between technology, well-being, and communication in an increasingly digitised society. The work reflects on the role of organisations in promoting human values, generating positive social impacts, and fostering quality of life. In this sense, it explores how AI and social marketing can become strategic allies in strengthening social cohesion, promoting collective well-being, and consolidating a culture of happiness in the digital age.
Keywords: Happiness management; Social marketing; Campus Tijuana